Implementation of a resource planning system within the framework of sustainable enterprise development - A. M. Levin; A. A. Ivliev (Путеводитель предпринимателя)
The subject of the research is the enterprise resource planning system. During the research, a conceptual research method was used to develop a master plan for the implementation of the S–ERP system. It was found that ERP systems provide broad benefits and opportunities for the entire organization, support the organization in the exchange and transfer of information between all functions and departments, and help achieve the goals and objectives of the organization.